Decision-Making Framework of Requirement Engineering Barriers in the Domain of Global Healthcare Information Systems. (15th February 2022) - Hamza, Muhammad; Akbar, Muhammad Azeem; Alsanad, Abeer Abdulaziz; Alsuwaidan, Lulwah; AlSagri, Hatoon S.; Al-Alshaikh, Halah Abdulaziz; Kanwal, Maliha
Abstract : The smart healthcare information system offers several benefits including effectively reducing the cost and risk of medical procedures, improving the utilization efficiency of medical resources, promoting exchanges and cooperation in different regions, pushing the development of telemedicine and self-service medical care, and ultimately connecting people (patients and medical teams). The development of smart healthcare information systems in a globally distributed environment is a swiftly followed paradigm in the recent era. The development and implementation of a global healthcare information system (GHIS) are complicated as it faces several important problems that are more related to requirement engineering (RE). The ultimate aim of this research study is to explore and prioritize the barriers that would hinder the actual RE process in GHIS. To meet the research objective, 17 barriers of RE in GHIS have been identified through literature review and verified with practitioners using a questionnaire survey approach. Moreover, the analytical hierarchy process (AHP) approach was applied to rank the investigated barriers considering their significance for GHIS. The outcomes revolved that coordination is the most critical category for RE barriers in GHIS. Emotions and personal values, scope change, and creep are considered, and ad hoc exchange management and the absence of traceability are analyzed as the high-priority barriers to RE in GHIS. The findings of this study provide a robust framework that is beneficial for researchers and practitioners to consider the most critical barriers on a priority basis and develop the new strategies for RE process success in GHIS.